2018
DOI: 10.1037/xap0000145
|View full text |Cite
|
Sign up to set email alerts
|

The effects of prequestions on classroom learning.

Abstract: Studies have shown that prequestions-asking students questions before they learn something-benefit memory retention. Prequestions would seem to be a useful technique for enhancing students' learning in their courses, but classroom investigations of prequestions have been sparse. In the current study, students from an introductory psychology course were randomly assigned to receive prequestions over each upcoming lesson (prequestion group) or to not receive prequestions (control group). At the end of class, stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 32 publications
6
33
0
Order By: Relevance
“…The present study shows that the pretesting principle (or test‐potentiated learning) can be extended to having an effect on study activity and achievement in a college course. In short, this study supports the pretesting principle, which asserts that students learn better when they are asked to take practice tests before a lesson (Carpenter et al, 2018; Richland et al, 2009). The present study adds to the literature by directly identifying changes in learner's study behavior, namely how they allocate their study time.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The present study shows that the pretesting principle (or test‐potentiated learning) can be extended to having an effect on study activity and achievement in a college course. In short, this study supports the pretesting principle, which asserts that students learn better when they are asked to take practice tests before a lesson (Carpenter et al, 2018; Richland et al, 2009). The present study adds to the literature by directly identifying changes in learner's study behavior, namely how they allocate their study time.…”
Section: Discussionsupporting
confidence: 79%
“…Importantly, positive effects of taking practice tests have been demonstrated in classroom settings (Karpicke, 2017; McDaniel, Agarwal, Huelser, McDermott, & Roedigner, 2011; Roediger, Agarwal, McDaniel, & McDermott, 2011; Schwieren, Barenberg, & Dutke, 2017). For example, in a classroom study involving pretesting, Carpenter, Rahman, and Perkins (2018) found that asking college students to answer questions before a lecture improved subsequent performance on a quiz, but only for the pretested content. Overall, there is emerging evidence for the potential of the pretesting principle in classrooms.…”
Section: Introductionmentioning
confidence: 99%
“…This research has produced mixed results. Some experiments have found that pretesting improves subsequent retrieval of the pretested material, but does not benefit other, non-pretested information (Carpenter, Rahman, & Perkins, 2018;Pressley, Tanenbaum, McDaniel, & Wood, 1990;Richland et al, 2009;Toftness, Carpenter, Lauber, & Mickes, 2018). Other studies, by contrast, have found that pretesting improves memory for both pretested and nonpretested information (Carpenter & Toftness, 2017), or that pretesting does not significantly benefit retrieval at all (Geller et al, 2017).…”
mentioning
confidence: 99%
“…Thus, pretesting followed by studying can benefit learning. That pretesting effect has been demonstrated for science texts (e.g., Richland et al, 2009), video lectures (e.g., Toftness et al, 2017), and foreign language vocabulary (e.g., Potts & Shanks, 2014), as well as at various retention intervals (e.g., Kornell et al, 2009), in laboratory and classroom settings (e.g., Carpenter et al, 2018), and with pretesting in cued recall and multiple-choice format (e.g., Little & Bjork, 2016). Although benefits of pretesting are commonly limited to memory for directly tested materials (e.g., James & Storm, 2019;Toftness et al, 2017), transfer of learning to materials that were not directly tested has sometimes also been observed (e.g., Carpenter & Toftness, 2017;.…”
Section: Pretesting: the Benefits Of Errorful Generationmentioning
confidence: 85%